Pengaruh Menghafal Al-Qur’an terhadap Prestasi Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadits Kelas 4 di MI Al-Umm Klari Kabupaten Karawang - Fadillah, Muhammad Naufan; Mansyur, Masykur H; Ulya, Neng (AS-SABIQUN, 2023)
The Al-Qur'an Hadith subject at Madrasah Ibtidaiyah is one of the PAI lessons that emphasizes the ability to read and write the Al-Qur'an and Hadith correctly, as well as memorize short surahs in the Al-Qur'an, introduction the simple meaning or meaning of these short letters and hadiths about commendable morals to be practiced in everyday life through exemplary and habituation. Madrasah Ibtidaiyah Al-Umm strives to produce graduates who are successful in both academic and non-academic aspects. There are many factors that influence this success, one of which is to familiarize students with morals and thinking of the Qur'an, where one of the leading programs is memorizing the Qur'an. The purpose of this study was to determine the application of memorizing the Al-Qur'an Hadith in class 4 MI Al-Umm, to determine the effect of memorizing the Al-Qur'an on student achievement in the subject of Al-Qur'an Hadith. The research method used in this study is quantitative with a correlational type. The process of collecting data in this study is observation, questionnaires, and documentation. The population in this study were grade 4 students at MI Al-Umm, as many as 82 students became the sample. The results of the hypothesis testing showed that the Tcount was 1.355 <Ttable 1.99006 with Sig. (0.179) > α (0.05), meaning that there is a positive influence but does not have a significant effect on memorizing the Al-Qur'an on learning achievement of the Al-Qur'an Hadith so that the results of the study show that the effect of memorizing the Al-Qur'an on learning achievement Al-Qur'an Hadith of 2.2% while 97.8% is determined by other variables that are not examined.